Evaluation of the physical stability of SLN and NLC before and after incorporation into hydrogel formulations - Souto, EB (2004)
Aqueous dispersions of lipid nanoparticles are being investigated as drug delivery systems for different therapeutic purposes. One of their interesting features is the possibility of topical use, for which these systems have to be incorporated into commonly used dermal carriers, such as creams or hydrogels, in order to have a proper semisolid consistency. For the present investigation four different gel-forming agents (xanthan gum, hydroxyethylcellulose 4000, Carbopol(R)943 and chitosan) were selected for hydrogel preparation. Aqueous dispersions of lipid nanoparticles-solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC)-made from tripalmitin were prepared by hot high pressure homogenization and then incorporated into the freshly prepared hydrogels. NLC differ from SLN due to the presence of a liquid lipid (Miglyol(R)812) in the lipid matrix. Lipid nanoparticles were physically characterized before and after their incorporation into hydrogels. By means of rheological investigations it could be demonstrated that physical properties of the dispersed lipid phase have a great impact on the rheological properties of the prepared semisolid formulations. By employing an oscillation frequency sweep test, significant differences in elastic response of SLN and NLC aqueous dispersions could be observed.